Method for eliminating welding residual stress - CHEN MAOJIN; ZHANG HONGWEI; XUE LIUTAO; JI SIQI (2017)
The invention discloses a method for eliminating welding residual stress. The method comprises the steps that an X-ray diffraction (XRD) test is conducted on a welding part for surface welding residual stress testing, and welding residual stress surface layer data is obtained; a welding simulation model of the welding part is established, simulation data of the welding residual stress is calculated, and then the distribution law of the welding residual stress of the welding part is finally obtained; numerical simulation calculation of the vibration impact process is conducted by simulating the impact frequency and the impact amplitude on the basis of the distribution law of the welding residual stress, and then vibration impact parameters for eliminating the welding residual stress are obtained; the welding part is clamped in a drivable positioning workbench, the positions of an impact head and a welding part welding joint on the positioning workbench are adjusted, and impact treatment is conducted in the mod